2011
DOI: 10.21608/jappmu.2011.83397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graded Levels of Potato by-Product and Tomato Pomace on the Performance and Carcass Characteristics of Broiler Chickens.

Abstract: The objective of the present study was to evaluate the potato by-product (PB) and tomato pomace (TP) as unusual feedstuff in broiler diets in terms of performance and carcass characteristics. A total number of 504 one day old male Ross broiler chicks were used in the experiment. The by-products were added to the experimental diets at 8, 16 and 24 % of the diet. After that, the experimental diets were divided into two groups. The first group was supplemented with enzyme mixture while the other group was free of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Persia et al (2003) discovered a 15% reduction in feeding efficiency in broiler chicks aged 8 to 21 days due to inclusion of tomato pomace. According to Dorra et al (2011), birds fed tomato pomace at 8% and 16% levels had considerably higher feed intake and a lower FCR than the control group. Mohammed et al (2021) found that supplementing broiler chicks with 4 and 6% tomato pomace had no effect on FCR or daily feed consumption.…”
Section: Feed Intake and Feed Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Persia et al (2003) discovered a 15% reduction in feeding efficiency in broiler chicks aged 8 to 21 days due to inclusion of tomato pomace. According to Dorra et al (2011), birds fed tomato pomace at 8% and 16% levels had considerably higher feed intake and a lower FCR than the control group. Mohammed et al (2021) found that supplementing broiler chicks with 4 and 6% tomato pomace had no effect on FCR or daily feed consumption.…”
Section: Feed Intake and Feed Efficiencymentioning
confidence: 99%
“…weight gain and growth performance Dorra et al (2011) found that 5% tomato by-product meal (TBM) resulted in better live body weight in broilers. According to Hosseini-Vashan et al (2016), adding 5% tomato pomace to broiler diets enhanced body weight and performance under heat stress.…”
Section: Feed Intake and Feed Efficiencymentioning
confidence: 99%
“…These results agree with which found by Makled et al (2019) when supplemented chicken diets with potato chips scraps (PCS), potato starchy waste (PSW) at levels 5 and 10%. Also, Tork et al (2011) added potato by-products to the broiler diets at 8, 16 and 24 % of the diet. chicken diets on Carcass traits at 10 weeks of age.…”
Section: Carcass Traitsmentioning
confidence: 99%